Nira water bottle design in a bid to elevate Malaysian coconut industry - Marzuki, Ibrahim; Mohd Hisham, Omar; Nurul Izzatul Hanin, Kamal (2020)
The coconutstands asthe fourthmostimportant industrial crop in Malaysia. It produces a myriad of products including nira water, usually involvesthe use of plastic bottles. Data collection wasinitiated by literature reviews, followed by direct observations and interviews to gather additional information relevant to the research. Three main issues were identified, namely accelerated fermentation process, nira water sours rapidly and rainwater seeping into nira water. Design process started with the establishment of design statement, followed by the criterias of design, namely aesthetics, product function, and ergonomics. Ideas and basic principles of nira water bottle product were brainstormed at Design Conception stage, progressing to its amalgamation into a single design at the Design Embodiment stage. The next stage is Selected Design, where the researcher produced rendering, detailed drawing and full-scale model. Details of proposed materials and production process were also prepared. Design process was completed with nira water bottle design appreciation via Feldman theory that comprises of four steps, namely description, analysis, interpretation, and evaluation. With this new nira water bottle design, it is hoped that the issues faced by nira water entrepreneurs in Malaysia could be somewhat mitigated. Hopefully this researchwill be a step forward in enhancing and upgrading the Malaysian coconut nira water industry, which is now seen as a potential source of wealth for the country, in addition to be on par with the world's leading producers of nira water.